2017
DOI: 10.1088/1361-6528/aa8943
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of 2D semiconductor film growth with optical spectroscopy

Abstract: Real-time monitoring of the growth is essential for synthesizing high quality two dimensional (2D) transition-metal dichalcogenides with precisely controlled thickness. Here, we report the first real time in situ optical spectroscopic study on the molecular beam epitaxy of atomically thin molybdenum diselenide (MoSe2) films on sapphire substrates using differential reflectance spectroscopy. The characteristic optical spectrum of MoSe2 monolayer is clearly distinct from that of bilayer allowing a precise contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Differential reflectance spectroscopy (DRS), which measures the normalized difference between the reflectance of the bare surface and the surface covered by thin films, possesses an enhanced sensitivity to the surface modification and ultrathin film growth [2526]. This technique has been successfully applied to reveal the optical properties of 2D TMDCs [2,20] and, most recently, also to monitor the molecular beam epitaxy of monolayer MoSe 2 on sapphire substrates [27]. In the current work, we have applied an analogous technology, namely, differential transmittance spectroscopy (DTS), to realize the in situ real time study of the CVD growth of monolayer MoS 2 on Al 2 O 3 (0001) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Differential reflectance spectroscopy (DRS), which measures the normalized difference between the reflectance of the bare surface and the surface covered by thin films, possesses an enhanced sensitivity to the surface modification and ultrathin film growth [2526]. This technique has been successfully applied to reveal the optical properties of 2D TMDCs [2,20] and, most recently, also to monitor the molecular beam epitaxy of monolayer MoSe 2 on sapphire substrates [27]. In the current work, we have applied an analogous technology, namely, differential transmittance spectroscopy (DTS), to realize the in situ real time study of the CVD growth of monolayer MoS 2 on Al 2 O 3 (0001) surface.…”
Section: Introductionmentioning
confidence: 99%
“…[44] López-Posadas et al [45] used in situ differential transmittance spectroscopy to monitor the growth kinetics of MoS monolayers using the difference in transmittance of the underlying substrate (SiO /Si) after a given deposition time. A few other studies have also used various in situ optical characterization methods, including spectroscopic ellipsometry (SE) [46] and differential reflectance/transmittance spectroscopy (DRS/DTS), [47][48][49] as effective thin film growth monitoring techniques.…”
Section: Mechanisms Of Crystal Growth From Amorphous Precursorsmentioning
confidence: 99%
“…The assembly of a SE in-situ characterization system is more difficult than differential reflectance spectroscopy (DRS). Sun et al in 2017 introduced an in-situ study about molecular beam epitaxy (MBE) growth of MoS 2 using DRS [26]. The results showed that DR spectra was sensitive to detect growth and optical properties of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Castellanos-Gomez et al studied the relationship between the thickness of TMDCs and exciton energy by ex-situ DRS [23]. Combined with the [26], DRS technology has become one of the most promising technologies for in-situ detection of 2D material prepared by CVD.…”
Section: Introductionmentioning
confidence: 99%